2012
DOI: 10.1136/jnnp-2011-301339
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and a mutation with late onset of limb girdle muscular dystrophy 2B

Abstract: Objective and methodsDysferlin encoded by DYSF deficiency leads to two main phenotypes, limb girdle muscular dystrophy (LGMD) 2B and Miyoshi myopathy. To reveal in detail the mutational and clinical features of LGMD2B in Japan, we observed 40 Japanese patients in 36 families with LGMD2B in whom dysferlin mutations were confirmed.Results and conclusionsThree mutations (c.1566C>G, c.2997G>T and c.4497delT) were relatively more prevalent. The c.2997G>T mutation was associated with late onset, proximal dominant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 38 publications
4
59
1
9
Order By: Relevance
“…These patients differed from those with dysferlinopathy by their later age of onset (usually after 30 years of age) and discreetly raised serum CK level 22. In the present study, the clinical phenotype of Miyoshi myopathy is consistent with already reported phenotypes 4,8…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These patients differed from those with dysferlinopathy by their later age of onset (usually after 30 years of age) and discreetly raised serum CK level 22. In the present study, the clinical phenotype of Miyoshi myopathy is consistent with already reported phenotypes 4,8…”
Section: Discussionsupporting
confidence: 90%
“…It clinically resembles other myopathies which involves the distal musculature, especially the muscles of lower legs 3. The mutations in the DYSF gene are a major cause of this disease 4. It differs from LGMD2B, in which the proximal part of muscles are affected although other characteristics such as age of onset, higher creatine kinase (CK) levels, progressive disease pattern, and dysmorphology of muscles have been found as well 5…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…У 20 из 25 японских пациентов с клиническим ди-агнозом ММ выявили 16 разных мутаций в гене DYSF, 10 из которых были новыми [12]. В своей работе K. Nguyen и соавт.…”
Section: том 6 Volunclassified
“…First symptoms usually begin in a narrow age range around 19 years old, with exceptional cases starting from birth to 58 years old 35,36,37 (Table 2). Different from other limb girdle muscular dystrophies, subacute presentation may occur in about 25% of the patients.…”
Section: Dysferlinopathy (Lgmd2b)mentioning
confidence: 99%